Occult Celiac Disease in an Octogenarian Presenting with a Small Intestinal Adenocarcinoma - Hugh James Freeman (Canadian Journal of Gastroenterology)
An 85-year-old male initially presented with an obstructed upper gastrointestinal tract associated with a duodenal adenocarcinoma. Subsequent histological studies revealed occult celiac disease, an associated condition that otherwise would not have been recognized in this elderly patient. The celiac disease responded to a gluten-free diet, even in the presence of an intestinal adenocarcinoma. This report suggests that celiac disease and small bowel carcinoma may coexist more frequently than is appreciated.